Hubungan Tingkat Pengetahuan Pengawas Minum Obat (PMO) Penderita TBC dengan Perilaku Pencegahan Penularan TBC di Wilayah Kerja Puskesmas Jatiyoso Kabupaten Karanganyar - Prihantoro, Adi, Abi Muhlisin, SKM, M.Kep (2013)
Drugs Taking Supervisors (DTS) is someone who ensures adherence to medication with TB. DTS role in the treatment of tuberculosis patients is not only limited to the treatment of tuberculosis patients, but also to perform actions TB transmission to other family members. TB infection prevention behavior must be conducted in accordance with the recommendations specified eg home ventilation, disposal of sputum of patient, and so on. Knowledge about TB disease, particularly about modes of transmission and prevention of transmission is essential to the DTS can take measures to prevent the transmission of pulmonary TB well. This study aims to determine the relationship of knowledge Drugs Taking Supervisors (DTS) TB patient with infection prevention behavior TB in the region of public health district jatiyoso karanganyar regency.This research is deskripstif analytic cross sectional approach. The study population is taking medication oversight of all TB patients are still undergoing treatment at the region of public health district jatiyoso as many as 32 people and as many as 32 samples with a total sampling technique. Research instrument in the form of questionnaires. Techniques of data analysis using Chi Square and Fisher Exact Test. The study concluded that: (1) the level of knowledge of drugs taking supervisors (DTS) of TB disease in the public health district Jatiyoso mostly moderate, (2) behavioral of drugs taking supervisors (DTS) tuberculosis patients about prevention of tuberculosis in the public health district Jatiyoso most are moderate, and (3) there is a correlation between taking the drugs taking supervisors (DTS) TB patients with TB disease prevention behaviors in the public health district jatiyoso, Chi Square test results with SPSS for windows 16.0 p = 0.049 where p ≤ 0.05